2001
DOI: 10.1097/00005110-200106000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Hospital RNs??? Job Satisfactions and Dissatisfactions

Abstract: In a survey addressing work-related stress, 1,780 registered nurses (RNs) discussed the many variables affecting their job satisfaction, including: why they chose nursing, patient care issues, nurse manager roles, salaries and benefits, and intent to stay in nursing. Their responses may be painful for nursing management to read. Yet, if new candidates are to be attracted and existing RNs retained, satisfaction of RNs with their jobs must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 29 publications
6
78
0
6
Order By: Relevance
“…Various authors (Basson & Van der Merwe 1994;Buchan 2006;Cavanagh 1997;Jackson, Clare & Mannix 2002;Mitchell 2003;Oulton 2006;Tusaie & Dyer 2004) reported on these and similar problems, whilst an emphasis seems to be on financial and managerial problems and lack of recognition or autonomy, a high workload and low morale (Buchan 2006). Fletcher (2001) found in a study with professional nurses that they love the work they do but hate their job, mainly because of adverse working conditions. If this current situation continues, where entry into nursing seems outweighed by exits, with nurses either emigrating or discontinuing practice, the crisis will deepen unless strategies are developed not only to retain nurses but to empower them, attract new recruits into nursing and entice nurses who have left to return to the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors (Basson & Van der Merwe 1994;Buchan 2006;Cavanagh 1997;Jackson, Clare & Mannix 2002;Mitchell 2003;Oulton 2006;Tusaie & Dyer 2004) reported on these and similar problems, whilst an emphasis seems to be on financial and managerial problems and lack of recognition or autonomy, a high workload and low morale (Buchan 2006). Fletcher (2001) found in a study with professional nurses that they love the work they do but hate their job, mainly because of adverse working conditions. If this current situation continues, where entry into nursing seems outweighed by exits, with nurses either emigrating or discontinuing practice, the crisis will deepen unless strategies are developed not only to retain nurses but to empower them, attract new recruits into nursing and entice nurses who have left to return to the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Work schedules figure prominently in nurses' ratings of their job satisfaction, along with job security, salary, and fringe benefits. 12 Most of our key informants reported that their institutions do not require employees to rotate across shifts; once a nurse has been hired for a specific shift, such as evenings, the nurse will stay on that shift unless there is an explicit agreement to change. Most of the key informants said that their hospitals schedule staff using twelve-hour shifts, but some maintain eight-hour shifts or offer three-hour and five-hour shifts.…”
Section: Study Findingsmentioning
confidence: 99%
“…[14] According to Philip Kotler, satisfaction is the level of person"s felt state resulting from comparing a products" perceived performance (or outcome) in relation to the person"s expectations. [15] The gap between perceived service and expectation has given rise to the construct of service quality [16], [17], [18] and to the construct of satisfaction [19], [20] and according to Canel & Fletcher (2001); satisfaction is linked to performance level of the business [21]. Hence customer satisfaction is the key to business success which can be achieved only by understanding what customers" expect and how they perceive the quality of the service delivery.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%